27.6k views
4 votes
Please help!! (Picture above) can you please explain how you did it? I’m confused.

Please help!! (Picture above) can you please explain how you did it? I’m confused-example-1
User Tuya
by
4.8k points

1 Answer

6 votes

9514 1404 393

Answer:

9

Explanation:

(f ◦ g)(3) = f(g(3))

Each of the coordinate pairs for g correspond to ...

(x, g(x))

Then g(3) can be found by looking for the pair that has 3 in the first location. That ordered pair is ...

(3, 4)

so we know that g(3) = 4.

Now, we know that f(g(3)) = f(4). This tells us to look for the ordered pair in the f relation that has 4 as its first value. That ordered pair is ...

(4, 9)

so we know that f(4) = 9.

__

In summary, ...

(f ◦ g)(3) = f(g(3)) = f(4) = 9

User Pschueller
by
4.5k points